Improving Academic Achievement for Islamic Religious Education Students through Lecturer Competence and Digital Learning Media - Siti Maryam Munjiat; Abdul Rifa’i; Cecep Sumarna; Didin Nurul Rosidin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
This study aims to determine the quality improvement of Islamic religious education students at XYZ Islamic University through lecturer competence and digital learning media. The method used is a quantitative method with a survey approach. The data was obtained by giving questionnaires to 63 respondents in this study. The questionnaire given to the respondents tested the validity and reliability so that the questionnaire was declared valid and had a level of reliability. The data obtained were tested using classical assumptions and analyzed using multiple linear regression. The results obtained in testing the hypothesis show that partially and simultaneously, the lecturer competence and digital learning media on the quality of Islamic religious education students have a positive and significant influence. This result is indicated by an Adjusted R Square of 0.247, which means that for every increase in the variable of lecturer competence and digital learning media by one, the student's quality also increased by 24.7%, assuming that other variables were considered constant.